Comparison of balance and function in the long term after all arthroscopic ATFL repair surgery - Ayas, İnci Hazal; Çiçeklidağ, Murat; Dağlı, Beyza Yazgan; Bircan, Resul; Tokgöz, Mehmet Ali; Çıtaker, Seyit; Kanatlı, Ulunay (Archives of orthopaedic and trauma surgery, 2023)
Introduction We compared the balance, ROM, clinical scores, kinesiophobia and functional outcomes of patients after all-arthroscopic ATFL repair surgery with the non-operated side and healthy control group. Materials and methods Twenty-five patients with follow up time 37.32 ± 12.51 months and twenty-five healthy controls participated in the study. Postural stability was evaluated with the Biodex® balance system by measuring overall (OSI), anterior–posterior (API), and mediolateral (MLI) stability index. Dynamic balance and function were measured using the Y-balance test (YBT) and single-leg hop test (SLH). Limb symmetry index for SLH and contralateral comparisons (YBT, OSI, API, MLI) was performed. The AOFAS score and the Tampa Scale of Kinesiophobia (TSK) were applied. Two subgroups were created (with OLT and without OLT). Results There was no statistically significant difference between subgroups. There was no statistically significant difference between bilateral OSI, API, MLI values and YBT anterior reach distances of all groups. Single leg OSI (0.78 ± 0.27/0.55 ± 0.12), API (0.55 ± 0.22/0.41 ± 0.10), and MLI (0.40 ± 0.16/ 0.26 ± 0.08) values were significantly worse and YBT posteromedial (73.88 ± 15.70/89.62 ± 12.25), posterolateral reach (78.03 ± 14.08/92.62 ± 8.25) and the SLH distance (117.14 ± 27.84/165.90 ± 20.91) were significantly lower on the patients than controls ( p < 0.05), respectively. In contralateral comparisons, all reach distances on YBT were similar and SLH limb symmetry index of the operated side was 98.25%. AOFAS scores of the patients were 92.62 ± 11.13, TSK scores were 46.45 ± 11.32, and 21 patients (84%) had kinesiophobia. Conclusion AOFAS score, limb symmetry index, and bilateral balance of the patients were successful; however, there is single-leg postural stability insufficiency and kinesiophobia. Although the extremity symmetry index of the operated side of the patients was 98.25, the fact that these values are lower than those of the healthy control may have been caused by kinesiophobia. During the long-term rehabilitation, kinesiophobia should be considered and single-leg balance exercises should be monitored during the rehabilitation period. Level of evidence Level III.